2018
DOI: 10.1111/jir.12489
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of social‐environmental variables on self‐injurious behaviour in adolescent boys with fragile X syndrome

Abstract: Social-environmental variables appeared to maintain SIB in a significant proportion of boys with FXS. Given that pharmacological treatments for SIB have limited efficacy in this population, the potential role of social-environmental factors on SIB should be examined before pharmacological treatments are implemented for these behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…The prevalence of behavior problems observed in this review is in general agreement with previous findings for different behavior problems. This is the case for the prevalence of attention and ADHD-related problems [ 114 ], and clinical range [ 115 ], although even higher scores were found in boys (77%) in other studies [ 116 ]; for the prevalence of aggression and severity rates [ 117 , 118 ], and self-injurious behavior [ 118 , 119 , 120 , 121 ], although higher prevalence has been found in studies with functional analyses [ 122 ]; and for the prevalence of thought problems in the clinical range [ 116 ]. Low percentages in the clinical range for delinquent behavior align with studies finding scores for this behavior in the normal range [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of behavior problems observed in this review is in general agreement with previous findings for different behavior problems. This is the case for the prevalence of attention and ADHD-related problems [ 114 ], and clinical range [ 115 ], although even higher scores were found in boys (77%) in other studies [ 116 ]; for the prevalence of aggression and severity rates [ 117 , 118 ], and self-injurious behavior [ 118 , 119 , 120 , 121 ], although higher prevalence has been found in studies with functional analyses [ 122 ]; and for the prevalence of thought problems in the clinical range [ 116 ]. Low percentages in the clinical range for delinquent behavior align with studies finding scores for this behavior in the normal range [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two raters independently classified cases without obvious trends and large response reductions in the conditions of interest (i.e., clear cases) with 100% agreement and came to a consensus on cases of low‐to‐moderate response reductions in the conditions of interest or with trends (i.e., unclear cases), which were selected for further discussion. Overall, 31 (25%) unclear cases required discussion among the raters (Ava, Bobby1, Brian1, Chad2, Charlene, Charlie, Christie, Dexter, Jack, Jamie1, Jamie2, Joey, Laura, Libby, Marc, Mark, P1 [Woods et al, 2013], P10, P17 & P22 [Healy et al, 2013], P8 [Hall et al, 2018], Peter1, Peter3, Rob, Ross, Sharon, Timmy1, Timmy2, Tina, Wyatt). The final consensus corrected the logically derived outcome of 15 (12%) datasets (Ava, Brian1, Chad2, Charlie, Christie, Jack, Janey, Joey, Laura, Mark, P1 [Woods et al, 2013], P8 [Hall et al, 2018], Timmy2, Tina, Wyatt).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 31 (25%) unclear cases required discussion among the raters (Ava, Bobby1, Brian1, Chad2, Charlene, Charlie, Christie, Dexter, Jack, Jamie1, Jamie2, Joey, Laura, Libby, Marc, Mark, P1 [Woods et al, 2013], P10, P17 & P22 [Healy et al, 2013], P8 [Hall et al, 2018], Peter1, Peter3, Rob, Ross, Sharon, Timmy1, Timmy2, Tina, Wyatt). The final consensus corrected the logically derived outcome of 15 (12%) datasets (Ava, Brian1, Chad2, Charlie, Christie, Jack, Janey, Joey, Laura, Mark, P1 [Woods et al, 2013], P8 [Hall et al, 2018], Timmy2, Tina, Wyatt). Datasets that could not be identified with any of the three proposed patterns were assigned to the other category.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to initiation of treatment, a member of the study team, who was a Board Certified Behavior Analyst (BCBA), traveled to the child’s home to conduct a functional analysis (FA) of the child’s problem behavior [ 60 ]. Briefly, six FA test conditions (i.e., ignore , attention , tangible , social escape , academic escape , and transition escape ) and one control condition ( play ) were conducted at least 4 to 6 times over 2 days in the child’s home [ 33 , 60 ]. In the ignore condition, the child was observed with no leisure items (e.g., toys) in the room, and caregivers were coached to ignore the child’s problem behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Although treatments for FXS are often considered from a medical perspective, several studies have shown that problem behaviors displayed by children with FXS may be shaped and maintained by operant learning processes such as positive and/or negative reinforcement [ 30 33 ]. For example, if a child typically receives attention from others when he/she engages in problem behavior, the child’s problem behavior may be positively reinforced by attention.…”
Section: Introductionmentioning
confidence: 99%